The Dynamics of Plug Zones in Elasto-Plastic Flows in Unsteady Flow in Circular Tubes - Letelier-Sotomayor, M; Stockle-Henriquez, J; Siginer, D (2012)
Purely oscillatory flow of an elasto-plastic fluid in round tubes is analyzed. A combined linear Maxwell-Bingham model is used to characterize the fluid behavior. Copyright © 2012 by ASME.